Does Nimodipine, a Selective Calcium Channel Blocker, Impair Chondrocyte Proliferation or Damage Extracellular Matrix Structures? - Kaplan, Necati; Yilmaz, Ibrahim; Karaarslan, Numan; Kaya, Yasin E.; Sirin, Duygu Y.; Ozbek, Hanefi (Current Pharmaceutical Biotechnology, 2019)
Background: The study aimed to investigate the effects of the active ingredient, nimodipine, on chondrocyte proliferation and extracellular matrix (ECM) structures in cartilage tissue cells. Methods: Chondrocyte cultures were prepared from tissues resected via surgical operations. Nimodipine was then applied to these cultures and molecular analysis was performed. The data obtained were statistically calculated. Results: Both, the results of the (3-(4,5 dimethylthiazol2-yl)-2,5-diphenyltetrazolium (MTT) assay and the fluorescence microscope analysis [a membrane permeability test carried out with acridine orange/ propidium iodide staining (AO/PI)] confirmed that the active ingredient, nimodipine, negatively affects the cell cultures. Conclusion: Nimodipine was reported to suppress cellular proliferation; chondroadherin (CHAD) and hypoxia-inducible factor-1 alpha (HIF-1α) expression thus decreased by 2.4 and 1.7 times, respectively, at 24 hrs when compared to the control group (p < 0.05). Furthermore, type II collagen (COL2A1) expression was not detected (p < 0.05). The risk that a drug prescribed by a clinician in an innocuous manner to treat a patient by relieving the symptoms of a disease may affect the proliferation, differentiation, and viability of other cells and/or tissues at the molecular level, beyond its known side effects or adverse events, should not be forgotten.
Keywords: type II collagen